Sonographic biometry of apparently normal parotid gland among adults in Asaba, South-South Nigeria - Mbonuejike, Ugwu Stephen; Uche, Chiegwu Hyacienth; Kelechi, Nwodo Victor; Daniel, Omojola Akintayo (Bangabandhu Sheikh Mujib Medical University Journal, 2024)
Background: Detecting subtle changes in the parotid gland size can be difficult when there are no established reference values in a specific area. This can affect patient management and delay early detection of diseases. Therefore, the objective of this study was to describe the size of the parotid gland of adult Nigerian people. Methods: This cross-sectional study included apparently healthy adults. The parotid glands were scanned in various sections using a 7.5 MHz probe after applying ultrasound gel. Each dimension was measured twice, and the mean value was calculat-ed. The 95% reference rages (mean ± 1.96 standard deviation) were described for various dimensions of the parotid glands. Results: Four hundred healthy adults participated in the survey. Their mean (standard deviation) age was 38.6 (14.6) years. The mean (95% reference range) of both parotid lengths was 4.7 (4.1 – 5.3) cm. The right and left parotid transverse sizes were 3.8 (3.4 – 4.2) and 3.7 (2.9 – 4.5) respectively. The right and left parotid depths lateral to the mandible were 0.8 (0.4 – 1.2) and 0.9 (0.3 – 1.5), parotid depths dorsal to the mandible were 2.3 (1.7 – 2.9) and 2.2 (1.8 – 2.6), and parotid volume were 20.3 (13.3 – 27.1) and 19.8 (14.3 – 25.3) cm3. No significant difference was seen between the right and left parotid glands in men and women. Conclusion: This study delineates the mean and reference range values of parotid glands among healthy adults of Nigeria which can be used for clinical decision making.